Optimization of Carbopol 940 Coriander Leaf Extract Gel (Coriandrum sativum L): Analysis of Physical Properties : EFFECT OF CARBOPOL 940 CONCENTRATION ON PHYSICAL PROPERTIES OF CORIANDER LEAF EXTRACT GEL (CORIANDRUM SATIVUM L.) - Nugraha, Davit; Yusuf, Anna; Rahmah KR, Siti; Wahlanto, Panji; Fawziah, Cindyvia (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
Topical gels are widely used because they are convenient to apply, easily absorbed, and have good stability. Carbopol 940 is one of the thickening agents often used in gel formulations because it can produce high viscosity at low concentrations and is compatible with various active ingredients. In gel formulation, the selection of Carbopol 940 concentration is very important to determine physical properties such as viscosity, pH, spreadability, and stability. Coriander leaves (Coriandrum sativum L.) contain bioactive compounds such as flavonoids, tannins, and saponins that have potential as antioxidants and antimicrobials. This study aims to examine the effect of Carbopol 940 concentration on the physical properties of gel containing coriander leaf extract by experimental method with variation of Carbopol 940 concentration in coriander leaf extract gel formulation. The physical properties of the gel, such as viscosity, pH, spreadability, and stability, were tested using physicochemical parameters to evaluate the effect of Carbopol concentration on the quality of the preparation. Coriander leaves (Coriandrum sativum L.) contain bioactive compounds such as flavonoids, tannins, and saponins that have potential as antioxidants and antimicrobials. The results showed that the concentration of Carbopol 940 significantly affected the physical properties of the gel, including viscosity, spreadability, and pH. The conclusion shows that the optimal formulation of Carbopol 940 can produce coriander leaf extract gel with physical properties that meet the requirements of topical drugs. Keywords: Gel, Coriander Leaf Extract, Formulation, Physical Properties Test